2021
DOI: 10.1038/s41589-021-00840-4
|View full text |Cite
|
Sign up to set email alerts
|

Designer membraneless organelles sequester native factors for control of cell behavior

Abstract: Subcellular compartmentalization of macromolecules increases flux and prevents inhibitory interactions to control biochemical reactions. Inspired by this functionality, we sought to build designer compartments that function as hubs to regulate the flow of information through cellular control systems. We report a synthetic membraneless organelle platform to control endogenous cellular activities through sequestration and insulation of native proteins. We engineer and express a disordered protein scaffold to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 58 publications
0
83
0
Order By: Relevance
“…One of the biggest challenges is spatiotemporal control over the time-programmed condensation and disassembly of the coacervate. The time-programmed phase behavior is currently available by changes in pH, temperature, ionic strength, light (UV), and more recently by enzyme-mediated catalytic activity ( Shin et al, 2017 ; Schuster et al, 2018 ; Martin et al, 2019 ; Wheeler et al, 2019 ; Garabedian et al, 2021 ). Furthermore, by converting chemical fuels, the coacervate droplet could behave like a protocell capable of self-division, making it an ideal model for approaching the dynamic complexity of living cells ( Zwicker et al, 2017 ; Donau et al, 2020 ; Karoui et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the biggest challenges is spatiotemporal control over the time-programmed condensation and disassembly of the coacervate. The time-programmed phase behavior is currently available by changes in pH, temperature, ionic strength, light (UV), and more recently by enzyme-mediated catalytic activity ( Shin et al, 2017 ; Schuster et al, 2018 ; Martin et al, 2019 ; Wheeler et al, 2019 ; Garabedian et al, 2021 ). Furthermore, by converting chemical fuels, the coacervate droplet could behave like a protocell capable of self-division, making it an ideal model for approaching the dynamic complexity of living cells ( Zwicker et al, 2017 ; Donau et al, 2020 ; Karoui et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The above-mentioned observations on the specific localization either inside or boundary of the droplet, depending on the conformation of giant DNA molecule is expected to stimulate further studies on the function of micro phase-segregation in living cellular systems [15][16][17][18][19][20][21][22]. Recently, we have shown that red-blood cells and epithelial cells are spontaneously entrapped into DEX-rich droplets under the condition of phase-separation with DEX/PEG aqueous solution [52].…”
Section: Plos Onementioning
confidence: 99%
“…In an aqueous solution of a mixture of semiflexible and flexible polymers, similar to the usual solution conditions for cytoplasm, semiflexible polymers are depleted into a folded compact state or a segregated state by self-assembly [ 12 14 ]. In relation to the segregation phenomenon, or w/w phase separation in aqueous solution with multiple macromolecules, membraneless organelles, such as nucleolus, ribosomes, P-body, and stress granules, have recently been attracting considerable interest in the biological sciences [ 15 17 ]. The stability of these membraneless organelles, together with experimental studies to construct their models [ 17 , 18 ], have frequently been interpreted in terms of liquid-liquid phase separation [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations